Effect of Post-grazing Sward Height on Ingestive Behavior, Dry Matter Intake, and Milk Production of Holstein Dairy Cows - Menegazzi, Gabriel; Giles, Pamela Yanina; Oborsky, Matías; Fast, Oliver; Mattiauda, Diego Antonio; Genro, Teresa Cristina Moraes; Chilibroste, Pablo (Frontiers in Animal Science, 2021)
The sward height is strongly related to the daily dry matter intake of grazing dairy cows, which consequently determines the animal performance. Despite that, few studies have explored the potential to increase milk production managing the post-grazing sward height. An experiment was carried out to evaluate the effect of three defoliation intensities on a Lolium arundinaceum based pasture on the behavior, dry matter intake and milk production of dairy cows. Three post-grazing sward height were tested: 15 (TL), 12 (TM) and 9 (TC) cm. Thirty-six autumn-calving Holstein cows were grouped by parity (2.6 ± 0.8), body weight (618 ± 48) kg and body condition score (2.8 ± 0.2) and randomized to the treatments. The pasture was accessed from 08:00 to 14:00 h and 17:00 to 03:00 h. The cows were not supplemented. Daily grazing time averaged 508 ± 15 min and was not affected by treatment. The reduction of post-grazing sward height increased the length of the first grazing session in the morning and the afternoon. The number of grazing sessions was greater on TL than on TM, with no difference in TC. The number of feeding stations visited was greater on TL than on TC, and neither of them differed from TM. Dry matter (DM) intake was greater on TL and TM than on TC (17.8 vs. 14.7 kg DM). Milk production during the paddock occupation period was 13.1, 16.2 and 18.7 kg/day for TC, TM and TL, respectively. The milk concentration did not differ between treatments. The cows on the lower defoliation intensity achieved a selective behavior resulting in high digestible dry matter intake and consequently higher milk production. The cows on TM adopted a compensation mechanism which allowed them to achieve the same dry matter intake as cows on TL, but lower milk production. The height and structure of the pasture on TC imposed the cows for a lower intake rate, although they were less selective, probably trying to compensate for the low ingestion.